Economic Development and Social change in Sri Lanka : a spatial and policy analysis - Groves, Paul A. (New Delhi : Manohar, 1996)
Contributed articles.
Includes bibliographical references (p. 371-374) and index.
Keywords: Migration, Internal -- Sri Lanka; Urbanization -- Sri Lanka; Sri Lanka -- Economic conditions